La técnica de reflexión sobre el examen para mejorar el rendimiento de los estudiantes - Flores Herrera, Jorge Rosendo (2019)
The purpose of this study was to improve the students’ performance who are registered in a physics course offered to the engineering careers of an Ecuadorian public university using the exam wrapper in combination with the cognitive and metacognitive strategies. The participants were 33 students. The instructional unit was Kinematics of a particle in one dimension. The time spent in teaching was 16 hours. The materials delivered were as follow: strategy to read a book, to solve problems and control. The instruments were the pretest and the posttest and a questionnaire to promote self-reflection. The procedure in the present study was as follows: (1) Explain the study unit. (2) Take the first exam. (3) Answer the questionnaire to promote self-reflection. (4) Explain the strategy for reading a book and practicing the strategy. (5) Explain the strategy to solve problems and practice the strategy. (6) Explain the control strategy and practice the strategy. (7) Take the second exam. The statistical analysis applied was the t-test for paired data. The results obtained show that the exam reflection technique improves the performance of students on the next exam.